Control of light absorbance using plasmonic grating based perfect absorber at visible and near-infrared wavelengths - Duc Minh Nguyen (Nature Portfolio, 2017)
Abstract Conventional metamaterial absorbers have multilayer designs, where the dielectric interlayer is sandwiched between a top patterned metallic structure and bottom metallic film. Here, we demonstrate that a highly polarization-sensitive perfect absorber canbe realized by replacing the bottom metallic film with a plasmonic grating. Designs for broadband and narrowband of wavelength are proposed and numerically investigated. The designed absorbers perform high light absorption, which is above 90% over the wavelength range of 0.4–1.4 µm for the broadband absorber and 98% for the absorption peak in case of the narrowband design, with a specific polarization of incident light. We find that the absorption is tunable by changing the polarization. Such absorbers offer new approach for active control of light absorbance with strong impacts for solar energy harvesting, light emitting and sensing.